Optimisation of phytate degradation in whole grain rice during germination processing using response surface methodology - Huei-Hong, Lee; Elisha, Yiu; Alvin-Lim-Teik, Zheng; Joseph-Choon-Fah, Bong; Su-Peng, Loh; Yiu, Pang Hung (UNIMAS Publisher, 2023)
Phytic acid (IP6), stored in seeds as metal salts known as phytates, binds to micronutrients and prevents its absorption by the human body. The germination process could improve cereal nutritional values by stimulating endogenous phytase activity and promoting phytate degradation. This study evaluated the physicochemical changes of phytates in rice cultivars with different IP6 contents, followed by optimisation of phytate degradation using response surface modeling. The magnitude of changes in IP6 content and phytase activity differed among rice cultivars. This suggested that the efficiency of germination treatments relied on the amount of natural phytic acid and phytase activity present in the rice grains. The cultivar “Tuan” was then selected and studied for the germination effect on phytate degradation using a central composite design. The cultivar gave a lower IP6 content, enhanced phytase activity and improved minerals bioaccessibility under acidic conditions. Acidic germination facilitated the degradation of phytate complexes in whole grain rice by making phytate complexes more soluble, accelerating phytase activity and thus, releasing mineral micronutrients from phytate globoids. The optimum germination condition was identified at pH 2.7, 25 °C over 12 h. In conclusion, germination processing facilitated phytate degradation in whole grain rice to make value-added rice products with low phytic acid and good mineral bioaccessibility.